The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1063/1.2773952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ga∕In ratio on the optical and electrical properties of GaInZnO thin films grown on SiO2∕Si substrates

Abstract: Amorphous GaInZnO and polycrystalline ZnO thin films are grown by rf magnetron sputtering. Their optical properties are investigated by spectroscopic ellipsometry. The optical gap of the GaInZnO film increases with the increase of Ga content and by annealing. These are attributed to the large band-gap energy of Ga2O3 and the structural relaxation after annealing, respectively. The changes in optical properties show a strong correlation to the device characteristics of GaInZnO thin film transistors: The turn-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…The recent oxide-based TFTs use mixed oxides of Ga, In or Sn, and Zn [6,8,34,60]. Mixing oxides enforces the desired amorphous character.…”
Section: Featurementioning
confidence: 99%
“…The recent oxide-based TFTs use mixed oxides of Ga, In or Sn, and Zn [6,8,34,60]. Mixing oxides enforces the desired amorphous character.…”
Section: Featurementioning
confidence: 99%
“…The optical band gap (E g ) can be obtained by extrapolating the straight-line portion of the (ahn) 2 vs. hn plot to the energy axis [25]. Considering the In 2 O 3 ($3.6 eV), Ga 2 O 3 ($4.9 eV), and ZnO ($3.3 eV) optical band gaps [18], the observed energy gaps were within a reasonable range. The inset of Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The XRD data of these thin films showed no characteristic peak for In-Ga-Zn-O (results not shown here), which confirmed that all of the films were amorphous. It is noteworthy that a-IGZO film remained in the amorphous phase even after annealing at 350 8C [18]. The thickness of the films, as estimated from the interference patterns of the XRR data (results not shown here), was almost equal $200 nm.…”
Section: Resultsmentioning
confidence: 88%
“…We have applied TOF-SIMS to study the temperature dependence of hydrogen behavior in the Pt/Ti/ GaInZnO thin film. A GaInZnO is one of transparent oxide materials which can be used for an active channel in the thin film transistor [12][13][14]. Kang et al [13] reported that GIZO surface is strongly reactive to the ambient oxygen.…”
Section: The Thermal Behaviors Of H O and Ti In Pt/ti/gainzno Thin Filmmentioning
confidence: 99%